2017
DOI: 10.14807/ijmp.v8i1.520
|View full text |Cite
|
Sign up to set email alerts
|

Haemoprotozoa Infection of Domestic Birds in Hilly Areas of Bangladesh

Abstract: The blood protozoa of two important domestic birds namely chickens (Gallus domesticus) and pigeon (Columba livia) reared in the hilly areas of Bangladesh were studied. A total of 400 birds (200 chicken and 200 pigeons) were examined of which 149 (37.3%) [95% CI] birds were found infected by one or more haemoprotozoan parasites. Haemoprotozoa belonging to three genera were identified. Pigeon 80 (40%) was recorded more susceptible to haemoprotozoa infection than chicken 69 (34.5%). 118 birds (29.5%) were found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 8 publications
9
4
3
Order By: Relevance
“…Gimba et al [6], Nakayima et al [19] and Nourani et al [24] have all reported these two avian haemosporidians, indicating that they are the most common in village chickens and have a global distribution. The present study also discovered mixed Plasmodium and Haemoproteus infections, which is consistent with previous findings [6,10,16,20,21,25].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Gimba et al [6], Nakayima et al [19] and Nourani et al [24] have all reported these two avian haemosporidians, indicating that they are the most common in village chickens and have a global distribution. The present study also discovered mixed Plasmodium and Haemoproteus infections, which is consistent with previous findings [6,10,16,20,21,25].…”
Section: Discussionsupporting
confidence: 93%
“…Plasmodium species (9.4%) was the most common haemosporidian in village hens, confirming the findings of other researchers who found Plasmodium species to be the most common haemosporidian infection in scavenging birds [4,6,8,19,21,32,37]. However, the Plasmodium prevalence rate in this study is lower than 11.4% in Maiduguri [11], 12.0% in Sokoto [40], 33.3% in Owerri [27], and 32.0% in Ibadan [33] of Borno, Sokoto, Imo, and Oyo States respective in Nigeria.…”
Section: Microfilariasupporting
confidence: 88%
See 1 more Smart Citation
“…This finding buttresses the finding of Naqvi et al (2017) who also reported mixed Plasmodium and Haemoproteus species infection in scavenging chickens. However, the finding of the present study is lower than 47.4% reported by Hasson (2015), but higher than 0.5% reported by Nath and Bhuiyan (2017). The difference in the reported prevalence rates of mixed Plasmodium and Haemoproteus species infections in chickens may partly be attributed to variation in geographic distribution of arthropod vectors.…”
Section: Discussioncontrasting
confidence: 86%
“…According to Nath et al (2014), prevalence of Leucocytozoon was 12% in chickens in Bangladesh. In hilly areas of Bangladesh, prevalence of haemoprotozoa in domestic bird was 60.6% in summer season, 36.7% in rainy and 23% in winter seasons (Nath and Bhuiyan, 2017). There is limited information on the epidemiology of these important haemoprotozoan parasites in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%